Journal Economics, business & accountancy : THE EFFECT OF AUDITOR QUALITY ON BOND RATING: THE TESTING OF "INFORMATION ROLE" AUDITORS IN INDONESIA - Wahyuni, Sri (PPPM Perbanas, 2013)
Measuring the company bond rating is important for the business nowadays. Auditor qualityis considered an important factor. Therefore, it is important to see the effect of auditor qualityon bond rating. The objective of this research is to investigate the relation between auditorquality characteristics (size, tenure and industry specialist auditors), and bond rating.Data used in this research are 1283 years-firm observation during 2000-2010.